Forage species introduction and evaluation on ancient levees and savanna in the eastern part of the Paiaguás subregion, Brazilian Pantanal - Filho, José Aníbal Comastri; Pott, Arnildo (Pesquisa Agropecuaria Brasileira, 1995)
Thirty grasses and 48 legumes were introduced in cleared ancient ridge, and 21 grasses and 21 legumes in savanna, in the eastern part of the Paiaguás subregion of the Brazilian Pantanal, from 1980 to 1985, with the objective of selecting adaptable forage plants. Germplasms were cultivated on 1.5 m x 3.0 m plots, two plots for each accession, one fertilized (F) and one non-fertilized (NF). Dry matter yield on F plots was higher than on NF plots only during the first year. An evaluation index (EI) of 0, 1, 2 and 3, indicated that the most promising forage species for ancient ridge were Brachiaria decumbens, with EI of 2.65 and 2.60, and B. humidicola with EI of 2.67 and 2.60 on F and NF plots, respectively. Calopogonium mucunoides was the most promising legume, with EI of 2.73 on F plot and 2.43 on NF plot. On savanna only B. humidicola was a promising species, with EI of 2.15 on both F and NF plots. No legume was so characterized. B. humidicola had the best soil cover, on both enviroriments, 90% on ancient ridge and 80% on savanna. Few pests and diseases occurred on the ridge.